New temperature reference cells for calibrating CSPRTs under adiabatic conditions. (2nd December 2014) - El Matarawy, A.A.; Ahmed, M.G.
Abstract : Two new miniature metallic sealed-cells containing the triple point of water, WTP (273.16 K) and the triple point of mercury, HgTP (234.3156 K) have been constructed for the realization of the International Temperature Scale of 1990 (ITS-90) at the National Institute of Standards (NIS-Egypt). The new cells will provide facilities for the calibration of Capsule-type Standard Platinum Resistance Thermometers (CSPRTs). The two cells will complete a multi-cells compartment in order to calibrate CSPRTs in one single experiment. The multi-cells compartment contains two other cells; the triple point of argon (83.8058 K) and the triple point of oxygen (54.3584 K) that has been already developed and characterized before [M.G. Ahmed, Y. Hermier, Development of an adiabatic calorimeter in the range 54 K–273 K in frame of a scientific collaboration LNE-NIS, AIP Conf. Proc.1552, 153 (2013)]. The system can calibrate two CSPRTs at once. The compartment is accommodated in an adiabatic calorimeter. With a special technique, the calorimeter could go down to a temperature of 52 K using liquid nitrogen and special pumping system.